Carrying Yourself: Self Antigen Composition of the Lymphatic Fluid - Santambrogio, Laura (Lymphat Res Biol, 2013)
Advances in proteomics methodology and instrumentation have allowed detailed characterization of the composition of lymph. Far from being a simple ultrafiltrate of blood plasma, lymph has been shown to carry a rich repertoire of proteins and peptides reflecting the tissue of origin and its physiological state. Peptides derived from lymph can be loaded on the MHCII proteins, particularly those present on immature and/or inactivated antigen presenting cells, and may play an important role in maintenance of peripheral tolerance.